If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 4 + -6 = 0 Reorder the terms: 4 + -6 + X = 0 Combine like terms: 4 + -6 = -2 -2 + X = 0 Solving -2 + X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + X = 0 + 2 Combine like terms: -2 + 2 = 0 0 + X = 0 + 2 X = 0 + 2 Combine like terms: 0 + 2 = 2 X = 2 Simplifying X = 2
| y=1.5(4)+5 | | 2x^2(2*2x)=8 | | x+x+1700=56100 | | y=1.5(0)+5 | | 2x^2(2*2x)=21 | | 2x^2(2*2x)=16 | | y=1.5(-2)+5 | | 26-x+4-6= | | 2x^2(2*2x)=0 | | 2x=56100-1400 | | 1y+1-12=4 | | -25=2x-9 | | x+1.5=5x-7.5 | | (x+1)(x+2)=20 | | 26-6+4= | | y=0.5(4)+6 | | y=0.5(0)+6 | | y=0.5(-2)+6 | | X+4-6=26 | | -18(3x-7y+9z)= | | 57-5x=4x+16 | | 8a+20-5a=7a | | -3a+5+4a=8-28 | | 3x+18=2x-12 | | X-4+6=26 | | 12j+4+1j=10j-3 | | 12j+4+j=10j-3 | | X^3+x^2-6x=0 | | 167-5x=6x+24 | | 9u-40=u-24 | | -900=-30(-6b) | | y=.494x-973.9 |